2014
DOI: 10.1021/jp500909x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Evolution of the Molecular Configuration of Oxo-Tungsten(VI) Species Deposited on the Surface of Titania

Abstract: The pH and temperature evolution of the molecular configuration of oxo-tungsten(VI) species deposited on TiO2 by equilibrium deposition filtration and the temperature evolution of the samples texture are studied using in situ Raman spectroscopy, DR spectroscopy, N2 adsorption–desorption measurements, and TGA. Prior to drying, WO4 2– monomers retained above a bridging surface hydroxyl of TiO2 through H bonding (with a Ti2OH···O–WO3 umbrella configuration) prevail at pH = 9. A pH decrease results in a gradual tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 69 publications
(155 reference statements)
2
27
0
Order By: Relevance
“…For clarity, only final equilibrated W (VI) spectrum was shown in Figure 2A. This spectrum illustrated IR bands associated with W-O symmetric (930 cm -1 ) and antisymmetric (830 cm -1 ) stretching due to strong inner-sphere type surface complexation of W (VI) with hematite surface as reported by earlier studies (Zorina and Syritso, 1972;Charton et al, 2002;Tomaszewicz et al, 2009;Kumar and Mohanta, 2011;Tribalis et al, 2014;Davantes and Lefevre, 2015;Rakshit et al, 2017). Subsequent time series spectra after 100 µM and 200 µM P additions were depicted to indicate the gradual growth of 1097 cm -1 IR band due to P surface complexation on hematite in the W +P mixed system (Figure 2A).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…For clarity, only final equilibrated W (VI) spectrum was shown in Figure 2A. This spectrum illustrated IR bands associated with W-O symmetric (930 cm -1 ) and antisymmetric (830 cm -1 ) stretching due to strong inner-sphere type surface complexation of W (VI) with hematite surface as reported by earlier studies (Zorina and Syritso, 1972;Charton et al, 2002;Tomaszewicz et al, 2009;Kumar and Mohanta, 2011;Tribalis et al, 2014;Davantes and Lefevre, 2015;Rakshit et al, 2017). Subsequent time series spectra after 100 µM and 200 µM P additions were depicted to indicate the gradual growth of 1097 cm -1 IR band due to P surface complexation on hematite in the W +P mixed system (Figure 2A).…”
Section: Resultssupporting
confidence: 52%
“…In our earlier study, we found strong W-O-W stretching band at 875 cm -1 for the pH envelope of W (VI) sorption on hematite in the pH range of 6 to 4.6 (Rakshit et al, 2017). Other researchers indicated that the presence of this band represents the formation of polytungstate species (Tribalis et al, 2014). Inspection of the IR bands in the present study reveal similar IR bands at 875-877 cm -1 in the difference spectra of pH (4.6-8.05, 5.05-8.05, and 6.05-8.05).…”
Section: Analysis Of In Situ Atr-ftir Spectra Of W (Vi) and P Binding Onmentioning
confidence: 72%
“…For higher concentrations, WO 3 nanoparticles (amorphous and crystallized) are evidenced. This contrasts with other supports (Al 2 O 3 [53,54], TiO 2 [55,56], ZrO 2 [57][58][59]) for which tungsten impregnation up to 4-5 W nm −2 leads to well-dispersed catalysts. On these supports, WO 3 nanocrystals are generally observed in the 4.5-9 W nm −2 loading range, while large bulklike WO 3 crystals can be observed beyond 9 W nm −2 [60].…”
Section: Structure Of Supported Tungsten Oxidesmentioning
confidence: 61%
“…Specifically, for W-adsorbed Fh samples at pH 6.5 and 4.5, and all W-adsorbed Fh-HA composite samples, the IR peak broadens towards higher frequencies. Interestingly, the W−O−W stretching vibrations, which are characteristic of polymeric tungstate species can appear at ~860−880 cm −1 (Davantès et al, 2016;Rakshit et al, 2017;Tribalis et al, 2014). Results therefore suggest the presnece of poly tungstate species on Fh and Fh-HA at pH≤6.5.…”
Section: Molecular W(vi) Adsorption Characteristicsmentioning
confidence: 80%